Exploring the Interplay of Intergenerational Transmission, Structural Inequalities, and Relative Resources in Domestic Violence: Evidence From a Nationally Representative Dataset - Berktaş, Ezgi (Journal of interpersonal violence, 2025)
Domestic violence persists as a significant social challenge affecting a considerable number of women globally. Some scholars have ascribed the inclination toward domestic violence to a “cycle of violence” spanning generations, while others have pointed out structural inequalities. Feminist researchers contend that a comprehensive understanding necessitates exploration within the social and institutional realms of gender inequality. While each of these perspectives contributes significantly to comprehending domestic violence, individually, they might not unveil the complete causal narrative. This study endeavors to address this gap by proposing an integrated model to elucidate domestic violence in the context of Türkiye, examining (a) the correlation between growing up in a violent household and the susceptibility to domestic violence, (b) the interrelation between structural factors and the vulnerability to domestic violence, and (c) the connection between a woman’s advantageous position in terms of the couple’s relative resources and the likelihood of experiencing domestic violence. To achieve this objective, multivariate micro-level analyses were conducted using nationally representative data from the 2014 Research on Domestic Violence Against Women in Türkiye. The outcomes affirm the significance of all three approaches, highlighting the value of integrated methodologies for a more profound comprehension of the etiology of domestic violence. This insight is crucial for the development of effective prevention programs. Furthermore, the findings highlight intra-parental violence exposure as the most robust risk factor or predictor for subsequent involvement in violent intimate relationships. As the initial study in Türkiye encompasses early-life experiences, structural inequalities, and the relative resources of couples, this research is poised to contribute significantly to the existing body of literature on domestic violence.